Late contributions of repetitive head impacts and TBI to depression symptoms and cognition. (18th August 2020) - Alosco, Michael L.; Tripodis, Yorghos; Baucom, Zachary H.; Mez, Jesse; Stein, Thor D.; Martin, Brett; Haller, Olivia; Conneely, Shannon; McClean, Michael; Nosheny, Rachel; Mackin, Scott; McKee, Ann C.; et al.
Abstract : Objective: To test the hypothesis that repetitive head impacts (RHIs), like those from contact sport play and traumatic brain injury (TBI) have long-term neuropsychiatric and cognitive consequences, we compared middle-age and older adult participants who reported a history of RHI and/or TBI with those without this history on measures of depression and cognition. Methods: This cross-sectional study included 13, 323 individuals (mean age, 61.95; 72.5% female) from the Brain Health Registry who completed online assessments, including the Ohio State University TBI Identification Method, the Geriatric Depression Scale (GDS-15), and the CogState Brief Battery and Lumos Labs NeuroCognitive Performance Tests. Inverse propensity-weighted linear regressions accounting for age, sex, race/ethnicity, and education tested the effects of RHI and TBI compared to a non-RHI/TBI group. Results: A total of 725 participants reported RHI exposure (mostly contact sport play and abuse) and 7, 277 reported TBI (n = 2, 604 with loss of consciousness [LOC]). RHI (β, 1.24; 95% CI, 0.36–2.12), TBI without LOC (β, 0.43; 95% CI, 0.31–0.54), and TBI with LOC (β, 0.75; 95% CI, 0.59–0.91) corresponded to higher GDS-15 scores. While TBI with LOC had the most neuropsychological associations, TBI without LOC had a negative effect on CogState Identification (β, 0.004; 95% CI, 0.001–0.01) and CogState One Back Test (β, 0.004; 95% CI, 0.0002–0.01). RHI predicted worse CogState One Back Test scores (β, 0.02; 95% CI, −0.01 to 0.05). There were RHI × TBI interaction effects on several neuropsychological subtests, and participants who had a history of both RHI and TBI with LOC had the greatest depression symptoms and worse cognition. Conclusions: RHI and TBI independently contributed to worse mid- to later-life neuropsychiatric and cognitive functioning.